Textural and Rheological Attributes of the Tubers of Some Exotic Cassava Genotypes - Sajeev, M.S.; Sreekumar, J.; Ravi, V.; Jyothi, A.N.; Sheriff, J.T. (JOURNAL OF ROOT CROPS, 2013)
Cassava or tapioca (Manihot esculenta Crantz) is one of the widely utilized tuber crops valued for its high carbohydrate content. Cassava is used after boiling as vegetable for consumption purpose. It is also processed into starch and flour. Textural properties of the raw and cooked tubers depend on variety, maturity, growing environment, physico-chemical properties, starch content and their properties. This study evaluated the textural properties of the raw and cooked tubers of selected exotic cassava genotypes. Also, the flours extracted from these genotypes were subjected to rheological characterisation by measuring their pasting properties. Cluster analysis was used to classify the genotypes based on the textural properties of raw tubers, texture profile of the cooked tubers and rheological properties of the flour. The textural and rheological properties significantly varied among the genotypes and based on these properties, the genotypes were classified into four groups: Group I- CE615, CE181, CE328,CE430, CE341, CE459, CI46, CE282, CI21 and CE440; Group II- CE423; Group III- CE365, CE364 and CE170 and Group IV- CE311, CE367, CE273, CE500, CE384 and CE215. This grouping based on the texture and rheology together was closer to the grouping based on the rheological properties alone, with the exception of CE423, which was most dissimilar in properties to the other genotypes. This clearly indicated that the rheological properties of starch can be the most important determining factor than the texture of the tubers for the classification of the cassava genotypes.